PENINGKATAN MUTU KUE TRADISONAL SERABI KHAS MANGGARAI NTT DENGAN PENAMBAHAN UBI JALAR UNGU (IPOMOEA BATATAS L.) - Helena Sensia Dawut; Lahming; Amiruddin Hambali (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This research is an experimental research aimed at determining the effect of adding purple sweet potato to the quality of traditional pancakes typical of Manggarai, NTT. The experimental design of this study used a completely randomized design (CRD) with a single factor experiment, namely the comparison of purple sweet potato and rice flour with 4 treatments, i.e. X0 (100% rice mouth), X1 (30%:65%), X2 (35%;65). %), X3 (40% to 65%) Parameters observed were moisture content, ash content, anthocyanin content and hedonic tests. (aroma, color, texture and taste). Observational data were tested by analysis of variance (ANOVA) at a significant level of 5%, if there were significant differences in the observations, then further tested using Duncan's test. The results showed that the use of purple sweet potato in the manufacture of traditional pancakes had a significant effect on chemical quality (ash content and anthocyanin content) and hendonic quality. (aroma, color and taste). However, the test results did not significantly affect the quality of water content and texture. The best concentration from the results of the research that has been done is the concentration of 40%:65% with a moisture content of 36.14%, ash content of 0.43%, aroma of 3.67%, color of 3.67, texture of 3.46%, taste of 3.57%, and 60% anthocyanin content.